Material flow cost accounting, perceived ecological environmental uncertainty, supplier integration and business performance: a study of manufacturing sector in Malaysia - Khaled M.A. Salim,; Amizawati Mohd Amir,; Maliah Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This article seeks to explore the implementation of Material Flow Cost Accounting (MFCA) across the manufacturing sector. The paper aims to understand the role of perceived ecological environmental uncertainty (PEEU) and supplierintegration (SI) on MFCA implementation, and thus subsequently examines the effect of MFCA implementation on firms’environmental and economic performance. The research model was empirically tested based on online-survey. The questionnaires were emailed to 1200 randomly selected industrial firms. The usable responses was 123 firms. The data was analysed using a structural equation modelling (SEM) approach through partial least square (PLS) software. The main results from survey of 123 companies showed low level of MFCA implementation. Further, the analysis of PLS indicated that companies which recognise bigger ecological environmental uncertainty are less motivated to implement MFCA. Tthe study also found that SI has a direct positive impact on MFCA implementation since companies which decided to implement MFCA were more likely able to achieve better environmental and economic performance. Thus, companies perceive the importance of being ecologically responsible and that such practice will increase companys’ prosperity in many ways, ecologically and economically.